Analysis of Language Politeness in English Learning at X IPA MA Raudlatul Ulum Klampis. - Millah, Karimatul; Kiptiyah , Mariyatul; Athena, Tera (Journal of Islamic Education, 2024)
This study aims to determine the politeness of students' language in learning English in class X IPA MA Raudlatul Ulum Klampis. This study uses triangulation of theory and sources, and data analysis is carried out using data tabulation techniques, followed by data presentation, interpretation, and conclusions. The results of the study show that the form of politeness in the interaction of teachers with students and between students in English learning discussion activities in the MA Raudlatul Ulum class. The results of the data analysis and subsequent discussion contribute to the academic understanding of politeness and provide practical implications for effective communication in the English learning process, providing the audience with valuable insights that can be directly applied in the classroom.